PROFESSIONAL EMPLOYMENT OF PHD PROGRAM GRADUATES AND SOME WAYS FOR IMPROVING PHD PROGRAMS - Boris I. Bednyi; Alexei A. Mironos; Larisa A. Ostapenko (Высшее образование в России)
We present the results of our study of employment of PhD program graduates of a multidisciplinary research university. Career paths of graduates who have defended their Candidate of Sciences thesis and of those who did not submit the thesis for defense are analyzed. Some features of the employment of graduates who were enrolled in PhD programs in natural sciences and social sciences and humanities are considered. The need is emphasized to study and take into account career paths of graduates and employers’ requirements when designing PhD programs of a new type.